Effect of cattle liquid manure fertilization and disinfectant on seasonal dynamics of Oribatida (Acari) in a permanent lowland meadow in Poland - Graczyk, Radomir; Seniczak, Stanisław; Wasińska-Graczyk, Beata (Biological Letters, 2011)
Oribatid mites have a favourable influence on soil fertility. The effect of cattle liquid manure fertilization (40 and 80 m3 ha-1) and disinfectant at 3 concentrations: 0.50% (fungicidal), 0.75% (bactericidal), and 3.00% (viricidal) on seasonal dynamics of Oribatida was investigated in a permanent lowland meadow in Poland. Cattle liquid manure without disinfectants reduced the density of oribatid mites, especially in the spring, except for a higher dose of fertilizer in the summer, which increased their density compared to the control plot. This fertilizer treated with the disinfectants differentiated the density of oribatid mites, i.e. reduced or increased it, compared to the control plots. However an increased density was observed only in summer, after application of the higher dose of fertilizer with fungicide or viricide. In the control plot, some species (Achipteria coleoptrata and Parachipteria bella) were rather abundant in the spring and autumn, and some other species (Liebstadia humerata and Scheloribates laevigatus) only in the spring. Cattle liquid manure and disinfectants changed the dynamics of density of these species. In the control plot the adults were slightly more abundant than the juveniles in the spring, but the juveniles dominated in the summer, and the adults dominated again in the autumn. Cattle liquid manure and disinfectants changed the age structure of oribatid mites. None of the experimental variants was favourable for Oribatida in all seasons.